THE EFFECT OF ORGANIZATIONAL CULTURE, EMPLOYEE ENGAGEMENT, AND JOB SATISFACTION ON EMPLOYEE ORGANIZATIONAL COMMITMENT AT PT AEROFOOD ACS SURABAYA - Irawati , Ferdina; Firdaus , Vera; Prapanca, Detak (ANTIS PUBLISHER, 2024)
This study is intended to examine the effect of organizational culture, employee engagement, and job satisfaction on organizational commitment of PT Aerofood ACS Surabaya. This type of research uses quantitative descriptive research methods. The location of the research conducted by the author to test the hypothesis is at PT Aerofood ACS - Surabaya which is located on Jl. Raya Juanda Airport Sidoarjo - East Java with a zip code of 61253. The number of respondents in this study were 100 people. This study uses questionnaire primary data with a Likert scale which is processed using SmartPLS with validity and reliability tests. The results obtained are employee engagement and job satisfaction have a significant effect on organizational commitment, while organizational culture has no significant effect.